A full-scale field experiment to study the hydrothermal behavior of the multilayer asphalt concrete pavement in cold regions. (18th January 2021) - Wu, Di; Jin, Long; Leng, Yanqiu; Hu, Mengling; Bi, Ran; Tang, Liyun; Gao, Zhihua; Yang, Gengshe
Highlights: A field experiment was performed to reveal the hydrothermal behavior of the MACP. Cement stabilized base is the moisture accumulation zone within MACP. Central part of the MACP develops a hydrothermal aggregation zone gradually. Abstract: As one of the widely used pavement materials and structures, the multilayer asphalt concrete pavement (MACP) presents evident heat absorption and hydrothermal accumulation behaviors, which is prone to severe frost and thaw damages in cold regions. A full-scale field experiment was performed to reveal the hydrothermal process within the MACP in Inner Mongolia of China. Based on the continuous three years' monitoring data, the freezing-thawing process, moisture features, and hydrothermal interactions of the MACP were analyzed. The results indicate that: (1) the MACP generates an important heat absorption and storage effect. A high heat flux accumulation zone forms at the central part of the MACP. Compared to the natural surface, the thawing freezing ratio at the bottom of the embankment enlarges 1.65 times armed with the MACP, meaning a dominant thawing process over a year cycle. (2) Under the influence of the thermal effect, moisture migration is considerably active within the MACP. The liquid water content of the MACP varies sharply with the decrease of the temperature. Then the cement stabilized base (CSB) and asphalt treated base (ATB) undergo the maximum and minimum liquid water contents, respectively. Furthermore, a core-shaped moisture accumulation area develops, coinciding with the features of the yearly distribution of the temperature. (3) The heat and mass transfer theory in the unsaturated porous medium was used to separate liquid water flux drove by the temperature gradient within the MACP. The temperature gradient driving effect mainly occurs in cold seasons. Under the impact of the temperature gradient, the ATB layer presents only downwards liquid water movement, while the CSB layer presents upwards and downwards liquid water movements.